Iatrogenic Left Main Coronary Ostial Stenosis after a Bentall Procedure in an Asymptomatic Young Man - Bernelli, Chiara (Texas Heart Institute, 2012)
Coronary ostial stenosis is a rare but potentially fatal sequela of aortic surgery. The clinical presentation can include acute coronary syndromes, ventricular arrhythmias, congestive heart failure, or sudden death. Herein, we present what we believe is the first reported case of asymptomatic iatrogenic left main coronary ostial stenosis. The patient was an active 34-year-old man who had undergone a modified Bentall procedure and was asymptomatic thereafter. Seven months after that operation, exercise stress testing showed electrocardiographic signs of asymptomatic myocardial ischemia at high workload, and coronary angiography revealed severe nonatherosclerotic left main ostial stenosis. Percutaneous coronary intervention and stenting of the unprotected left main stenosis was successful, and patency at 8 months was apparent on coronary angiography. The conventional treatment for coronary ostial stenosis, coronary artery bypass grafting, carries a high risk of perioperative infarction, morbidity, and death. We found that percutaneous coronary intervention with stenting yielded positive short- and long-term results and may provide an alternative to cardiac surgery in these high-risk patients. We recommend that physicians evaluate even asymptomatic patients for left main coronary ostial stenosis after aortic surgery so that early diagnosis and treatment can avert severe clinical manifestations.